THE INTEGRATION OF PROJECT-BASED TASK AND GROUP WORK IN EFL ACADEMIC WRITING: A MEANS TO PROMOTE LANGUAGE AND CONTENT - Ribut Sutjowati (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2014)
Writing is one of the English skills that have to be learnt by the students of the English department besides Reading, Speaking and Listening. For them it is not easy to write in English since they often feel that it is not an interesting activity especially if they are asked to write argumentative essay. Project-based task is one alternative that can build their motivation in writing. This project will involve the students starting from the beginning till the end of the process of writing. This paper presents the practice of integrating Project-based task and argumentative essay writing. It helps the lecturer and the students to create different and challenging activities in Critical Writing Class.